The influence of YouTubers on followers’ use intention - Corrêa, Stela Cristina Hott; Soares, João Luiz; Christino, Juliana Maria Magalhães; Gosling, Marlusa de Sevilha; Gonçalves, Carlos Alberto (Journal of research in interactive marketing, 2020)
Purpose This study aims to investigate the relationship between the follower’s engagement with YouTubers and his/her intention of using a brand they advertise or use. Self-connection, brand love and trust are mediating variables concerning the YouTuber–follower relationship and involvement is the antecedent variable of the engagement. Design/methodology/approach A survey was carried out and 272 YouTubers’ followers responded. The structural model was tested by covariance-based structural equation modeling using the software R, v3.6.0. Findings The present study reveals that the follower’s engagement with YouTubers presents itself within cognitive, affective and behavioural aspects; it rises from the involvement the followers have with their favourite YouTuber. Engagement, enhanced by self-connection, love and trust in the YouTuber, impacts the intention of use of a brand he/she indicates or uses. Practical implications YouTube is a relevant channel for advertising and promoting a brand. Hence, the company should bear in mind the fact that the YouTuber appointed to represent its image must be connected to the feelings and interests of their followers as well as those of the brands to be publicised. Originality/value The present research proposes a novel conceptual connection to engagement, established no longer by the brand of a product or service, but by YouTubers. It aims at rendering contribution to this subject as it investigates the correlation of use intention of a brand, subject to the engagement with a human brand, herein represented by YouTubers.